2021
DOI: 10.1002/adem.202100773
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial Perovskite Composite Fibers Spinning the Way to Flexible Solar Cells

Abstract: Hybrid halide perovskites have made significant progress in achievably high photoconversion efficiencies (>25%) and stability as a function of their chemical engineering realized by isomorphous substitution at all three sites in AMX3 composition. Whereas the focus of current research lies on planar (2D) devices, this work brings forth an innovative structural engineering concept based on direct electrospinning of the three major perovskite solar cell components, namely, photoabsorber, hole, and electron transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Electrospun nanofibers have attracted a lot of attention in scientific and industrial communities due to their unique properties, such as light weight, flexibility, controllable properties, and low cost, which have allowed them to be widely applied in many fields, e.g., energy generation and storage, sensors, drug delivery, filtration, etc. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The type of material (i.e., polymers and/or additives) and its properties (optical, electrical, mechanical, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrospun nanofibers have attracted a lot of attention in scientific and industrial communities due to their unique properties, such as light weight, flexibility, controllable properties, and low cost, which have allowed them to be widely applied in many fields, e.g., energy generation and storage, sensors, drug delivery, filtration, etc. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The type of material (i.e., polymers and/or additives) and its properties (optical, electrical, mechanical, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The type of material (i.e., polymers and/or additives) and its properties (optical, electrical, mechanical, etc.) determine their application area [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The properties of nanofibers can be optimized by manipulating their thickness, diameter, and orientation of nanofibers (their structure) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, additives such as copper (Cu), sodium (Na), and ethyl ammonium (EA) were examined. Cu compounds such as copper thiocyanate (CuSCN), copper oxides, (Cu x O), and copper iodide, were mainly used as hole-transport materials that replaced organic versions [9][10][11][12][13][14]. Although there have been many reports on the addition of alkali metals to perovskite precursor solutions [15][16][17][18][19][20][21][22][23], relatively few reported on the addition of Cu [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, copper (Cu), sodium (Na) and ethylammonium (EA) were focused on. Cu compounds are mainly used as hole transport materials, such as copper thiocyanate (CuSCN) and copper oxide (CuO or Cu2O), which are expected to be stable inorganic hole transport materials that can replace organic hole transport materials [1][2][3][4][5]. Many studies have been reported on the addition of alkali metals to perovskite precursor solutions [6][7][8][9][10][11], but relatively few studies have been reported on the addition of copper [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%